Law Enforcement Agency Identifiers Crosswalk (United States), 2000 ([Verlag nicht ermittelbar], 2004)
Researchers have long been able to analyze crime and law enforcement data at the individual agency level (see UNIFORM CRIME REPORTING PROGRAM DATA: [UNITED STATES] [ICPSR 9028]) and at the county level (see, for example, UNIFORM CRIME REPORTING PROGRAM DATA [UNITED STATES]: COUNTY-LEVEL DETAILED ARREST AND OFFENSE DATA, 1997 [ICPSR 2764]). However, analyzing crime data at the intermediate level, the city or place, has been difficult. To facilitate the creation and analysis of place-level data, the Bureau of Justice Statistics (BJS) and the National Archive of Criminal Justice Data (NACJD) created the Law Enforcement Agency Identifiers Crosswalk. The crosswalk file was designed to provide geographic and other identification information for each record included in either the Federal Bureau of Investigation's Uniform Crime Reports (UCR) files or BJS's Directory of Law Enforcement Agencies. The main variables for each record are the UCR originating agency identifier number, agency name, mailing address, Census Bureau's government identification number, UCR state and county codes, and Federal Information Processing Standards (FIPS) state, county, and place codes. These variables make it possible for researchers to take police agency-level data, combine them with Bureau of the Census and BJS data, and perform place-level, jurisdiction-level, and government-level analyses.